Penguatan Pemberian Pelayanan Prima Bagi Aparatur Desa Taluduyu Kecamatan Buntulia Kabupaten Pohuwato - Alfiyah Agussalim; Rahmatia Pakaya; Abdul Mukhlis Akuba (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Excellent service is one of the important aspects in improving the quality of life of the community, especially in public services at the village government level. This community service activity aims to improve the quality of public services in Taluduyunu Village and encourage active community participation in the service process, thereby creating transparency and public accountability. The method used in this service is to provide reinforcement in the form of education to all Taluduyunu Village government officials about the importance of excellent service to the community. Community service activities in Taluduyunu Village, Buntulia District, Pohuwato Regency, through several stages, starting from direct observation in the field to analyze needs, preparation of educational materials, implementation of service, to reporting the results of service. From the results of this service activity, it is hoped that it can increase the understanding and skills of Taluduyunu Village government officials, Buntulia District, Pohuwato Regency in providing fast, accurate, and quality services, as well as encouraging active community participation in village development. In addition, through this service program it is hoped that it can become a pilot model for other villages to improve the quality of public services through the provision of excellent and quality services.